Recent advances in the N-heterocyclic carbene (NHC)-organocatalyzed stetter reaction and related chemistry - Yetra, Santhivardhana Reddy; Patra, Atanu; Biju, Akkattu T. (Synthesis‐Stuttgart, 2015)
Recent developments in the N-heterocyclic carbene (NHC)-catalyzed umpolung of aldehydes followed by their interception with activated carbon–carbon double bonds, namely the Stetter reaction, are presented. Advances in the inter- and intramolecular versions of this reaction, enantioselective transformations as well as the use of unactivated olefins in this type of reaction are discussed.